2000
DOI: 10.1046/j.1525-1497.2000.12088.x
|View full text |Cite
|
Sign up to set email alerts
|

Who is at risk of nondetection of mental health problems in primary care?

Abstract: OBJECTIVE:To determine patient and provider characteristics associated with increased risk of nondetection of mental health problems by primary care physicians. DESIGN:Cross-sectional patient and physician surveys conducted as part of the Medical Outcomes Study. PARTICIPANTS:We studied 19,309 patients and 349 internists and family physicians. MEASUREMENTS AND MAIN RESULTS:We counted "detection" of a mental health problem whenever physicians reported, in a postvisit survey, that they thought the patient had a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
261
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(290 citation statements)
references
References 51 publications
20
261
2
2
Order By: Relevance
“…General Practitioners play a crucial role in the detection and referral of mental health problems in primary care (Borowsky, et al, 2000;Bradley, 2008;Copty, 2004;Copty & Whitford, 2005). In Ireland, this is highlighted by current mental health policy as outlined in 'A Vision for Change' (Republic of Ireland Department of Health and Children, 2006), which further augments the role of the GP as a conduit for access to a broad range of mental health services both public and private.…”
Section: Irish General Practitioner Referrals To Psychological Therapiesmentioning
confidence: 99%
“…General Practitioners play a crucial role in the detection and referral of mental health problems in primary care (Borowsky, et al, 2000;Bradley, 2008;Copty, 2004;Copty & Whitford, 2005). In Ireland, this is highlighted by current mental health policy as outlined in 'A Vision for Change' (Republic of Ireland Department of Health and Children, 2006), which further augments the role of the GP as a conduit for access to a broad range of mental health services both public and private.…”
Section: Irish General Practitioner Referrals To Psychological Therapiesmentioning
confidence: 99%
“…7,8 The quality of depression care in primary care also varies by patient race and ethnicity. Even when African Americans discuss emotional concerns, they are often not recognized as being depressed [9][10][11][12] and are less likely than whites to be referred to mental health specialists by their primary care physicians. 13 Attrition from psychotherapy and pharmacotherapy is also higher and rates of guideline-concordant care are lower for African Americans compared to whites.…”
Section: T He Majority Of Individuals With Depression In the Unitedmentioning
confidence: 99%
“…Black women had higher odds of initiating care in an outpatient mental health setting, but blacks and Latinas who initiated antidepressant use had much lower chances than white women of refilling a prescription. Prior research has revealed that depression preferences for treatment modality differ by race, with blacks and Latinas generally preferring psychotherapy over antidepressant medications (15,4547) As such, this finding may provide information about patient desire or willingness to refill a prescription or clinician response to patient preferences.…”
Section: Discussionmentioning
confidence: 99%